The human milk microbiome and factors influencing its composition and activity. Issue 6 (December 2016) - Gomez-Gallego, Carlos; Garcia-Mantrana, Izaskun; Salminen, Seppo; Collado, María Carmen
Summary: Beyond its nutritional aspects, human milk contains several bioactive compounds, such as microbes, oligosaccharides, and other substances, which are involved in host–microbe interactions and have a key role in infant health. New techniques have increased our understanding of milk microbiota composition, but few data on the activity of bioactive compounds and their biological role in infants are available. Whereas the human milk microbiome may be influenced by specific factors – including genetics, maternal health and nutrition, mode of delivery, breastfeeding, lactation stage, and geographic location – the impact of these factors on the infant microbiome is not yet known. This article gives an overview of milk microbiota composition and activity, including factors influencing microbial composition and their potential biological relevance on infants' future health.